2017
DOI: 10.1002/term.2528
|View full text |Cite
|
Sign up to set email alerts
|

The atrial appendage as a suitable source to generate cardiac‐derived adherent proliferating cells for regenerative cell‐based therapies

Abstract: Cardiac-derived adherent proliferating (CardAP) cells obtained from endomyocardial biopsies (EMBs) with known anti-fibrotic and pro-angiogenic properties are good candidates for the autologous therapy of end-stage cardiac diseases such as dilated cardiomyopathy. However, due to the limited number of CardAP cells that can be obtained from EMBs, our aim is to isolate cells with similar properties from other regions of the heart with comparable tissue architecture. Here, we introduce the atrial appendage as a can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…We Cell-based therapies and tissue engineering have long been investigated for their ability to deliver tissue regenerative adjuvant support. Atrial appendages were identified as niches for cardiac stem and progenitor cells and serve as a good autologous source of myocardial tissue for therapy due to their easy accessibility and relative redundancy for cardiac function (18,19).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We Cell-based therapies and tissue engineering have long been investigated for their ability to deliver tissue regenerative adjuvant support. Atrial appendages were identified as niches for cardiac stem and progenitor cells and serve as a good autologous source of myocardial tissue for therapy due to their easy accessibility and relative redundancy for cardiac function (18,19).…”
Section: Discussionmentioning
confidence: 99%
“…However, in the AAM and ECM patch groups, the fall in LVEF seemed considerably smaller in magnitude than that observed in the MI group. The acute declines in LVEF at one-week time-point postoperatively in AAM patch, ECM patch and MI groups were as follows: 18.03 (from 54.49±2.93% to 36.69±2.56%), 19.77 (from 52.15±3.10% to 32.38±2.96%) and 34.94 percent points (from 58.72±2.58% to 23.78±3.16%), respectively, with significant difference perceptible only between AAM patch and MI groups. However, since prevention of acute HF seemed evident in both patch groups, we hypothesize a considerable protective effect to occur by direct mechanical support, i.e.…”
Section: Myocardial Function Left Ventricular Ejection Fraction (Lvementioning
confidence: 97%
See 1 more Smart Citation
“…To date, preclinical studies of regenerative medicine identified useful therapeutic potential in the C-MSC and their paracrine activity 18 22 23 . Importantly, clinical trials in which the cell source is the heart are underway either with cardiosfere-derived cells or with subpopulations of C-MSC 13 24 25 .…”
Section: Discussionmentioning
confidence: 99%
“…21,22,[24][25][26][27][28][29][30][31][32][33] Several specific interventions have been identified to improve the maturation of hPSCderived cardiomyocytes including (i) addition of thyroid hormone, 34 (ii) application of electrical stimulation, 33,35,36 , (iii) mechanical loading 21,27,[37][38][39] , or (iv) co-culture with cardiac-specific cell types including endothelial cells 22 and cardiac fibroblasts 21,31,[40][41][42] or a mixture of fibroblast-like stromal cells. 37,43 A good understanding of the optimal cellular make up as well as reliable quality markers for cardiomyocytes and non-myocyte maturation should be instrumental to further improve the sophisticated architecture and function engineered myocardium.…”
Section: Cells and Their Requirements For Te-directed Remuscularizationmentioning
confidence: 99%